(untitled) (Indian Journal of Child Health, 2020)
Amid coronavirus disease (COVID-19) pandemic, recently a number of children who developed a significant systemic inflammatory response have been identified from various parts of the world. This syndrome has been described to have clinical features closely related to Kawasaki disease, toxic shock syndromes, bacterial sepsis, and macrophage activation syndromes. Clinical and laboratory manifestations of this multisystem inflammatory syndrome have been attributed to the antibodies produced against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Here, we report a case of a previously well 4-year-old female child who presented to us with multisystem inflammatory syndrome in children (MIS-C) following exposure to SARS-CoV-2 and was successfully managed with intravenous immunoglobulin (IVIGg) and IV steroids.